Gan - Shatz, Ruthie; Barash, Adi (Israel : Fig Films, 2003)
The Garden is a desolate section of Tel Aviv where young gay prostitutes and drug addicts gather. It's a territory for the dispossessed and for pickups, drug deals, and clashes with the law. The film follows a year in the life of two young men who have made the Garden their home: Nino, a 17-year-old Palestinian, in and out of jail and reformatories; and Dudu, an Arab-Israeli destroying himself through drug addiction. The filmmakers, ever mindful of the trust they have earned, create a powerfully honest film, affording Nino and Dudu the respect and dignity that are all too often denied them in their daily lives. Against the backdrop of the Israeli/Palestinian conflict, and the unease and ridicule still directed toward homosexuals, the two friends depend on each other for security and love. A poignant film that does not try to numb the pain or reduce the loneliness, Garden is ultimately about longing and belonging, and the elusive meaning of home.
Verzio Film Festival Submission
Duration: 01:23:00
Keywords: Israel